Pengaruh Harga Kamar dan Kualitas Pelayanan terhadap Keputusan Menginap di Westin Resort & Spa Ubud, Bali - Ni Wayan Cittin Atiramaniya; Ni Made Suastini; Nyoman Gede Mas Wiartha (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
This study aims to determine the influence of room price and service quality on the decision to stay at The Westin Resort & Spa Ubud, Bali. The population of this study comprises individuals who stayed at The Westin Resort & Spa Ubud, Bali, in the last month up to March, totaling 1250 people, with a sample size determined using simple random sampling technique amounting to 93 samples. Data collection method involved questionnaires analyzed using multiple linear regression analysis. The data analysis results show that room price and service quality have a positive and significant influence on the decision to stay. The regression value obtained is F-statistic of 36.852, which is greater than the critical F-value of 2.70. The strength of the relationship between Room Price (X1) and Service Quality (X2) as independent variables in this study with the percentage of Stay Decision as the dependent variable is 0.871. This indicates a very strong and positive relationship between the independent variables and the dependent variable. The magnitude of the influence of room price and service quality on the decision to stay is 75.8%. Recommendations from the researcher include enhancing room price strategies to compete with nearby hotels. Additionally, management should consider aligning prices with room quality to improve guest stay decisions. For future research, it is suggested to investigate other factors influencing stay decisions such as location, promotions, and advertising